1983
DOI: 10.1104/pp.73.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid-Induced Freezing Resistance in Cultured Plant Cells

Abstract: ABSTlRACTThe effect of abscisic acid (ABA) on the cold hardiness of cell suspension was investigted. Cell (2,(15)(16)(17). Because of the involvement of ABA in many environmental stresses, ABA has been proposed as a common mediator for plant stress response (5). However, the role of ABA in the adaptation of plants to freezing stress is not clear. Irving and Lamphear (13) were among the first to suggest that ABA may be involved in the cold hardening process.Two lines of evidence support the involvement of AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
2
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(142 citation statements)
references
References 17 publications
12
127
2
1
Order By: Relevance
“…This is in agreement with the observation that both drought and exogenous ABA treatments can mimic the effects of low temperatures and increase the freezing tolerance of several temperate species (Cloutier and Siminovitch, 1982;Chen and Gusta, 1983;Mantyla et al, 1995). Moreover, it has been shown that the endogenous levels of ABA increase in response to low temperature and water stress Lang et al, 1994).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…This is in agreement with the observation that both drought and exogenous ABA treatments can mimic the effects of low temperatures and increase the freezing tolerance of several temperate species (Cloutier and Siminovitch, 1982;Chen and Gusta, 1983;Mantyla et al, 1995). Moreover, it has been shown that the endogenous levels of ABA increase in response to low temperature and water stress Lang et al, 1994).…”
supporting
confidence: 77%
“…We have also found that the levels of RCI2A and RC/2B transcripts increase in response to ABA, another treatment that enhances freezing tolerance (Chen and Gusta, 1983) and induces the expression of the majority of coldinducible genes (Hughes and Dunn, 1996). Endogenous levels of ABA have been shown to transiently increase in response to low temperature and water stress (Lang et al, 1994) with kinetics that parallel those of the cold-induced RC12 mRNA accumulation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…ABA can also function as a drought related signal from the roots to the top of the plants (Davies and Zhang 1991). The role of ABA in regulating freezing stress tolerance has also been documented in a number of studies (Chen andGusta 1983, Reaney et al 1989).…”
Section: Genetic Aspects Of Adaptationmentioning
confidence: 99%
“…Heat tolerance was determined by incubating 0.40 g fresh weight of cells at 42.5OC for up to 160 min, with cells collected at 20-min intervals for viability assessment. Viability was assessed by regrowth, TTC reduction, and fluorescein diacetate staining (Chen and Gusta, 1983). In regrowth assays, 0.15 to 0.20 g fresh weight of stressed cells were transferred to fresh Erickson's niedium and increases in fresh weight were determined after 10 d at 25OC.…”
Section: Cell Cultures and Viability Assaysmentioning
confidence: 99%